Major genetic discontinuity and novel toxigenic species in Clostridioides difficile taxonomy - Knight, DR; Imwattana, K; Kullin, B; Guerrero-Araya, E; Paredes-Sabja, D; Didelot, X; Dingle, KE; Eyre, DW; Rodríguez, C; Riley, TV (eLife Sciences Publications, 2021)
Clostridioides difficile infection (CDI) remains an urgent global One Health threat. The genetic heterogeneity seen across C. difficile underscores its wide ecological versatility and has driven the significant changes in CDI epidemiology seen in the last 20 years. We analysed an international collection of over 12,000 C. difficile genomes spanning the eight currently defined phylogenetic clades. Through whole-genome average nucleotide identity, and pangenomic and Bayesian analyses, we identified major taxonomic incoherence with clear species boundaries for each of the recently described cryptic clades CI–III. The emergence of these three novel genomospecies predates clades C1–5 by millions of years, rewriting the global population structure of C. difficile specifically and taxonomy of the Peptostreptococcaceae in general. These genomospecies all show unique and highly divergent toxin gene architecture, advancing our understanding of the evolution of C. difficile and close relatives. Beyond the taxonomic ramifications, this work may impact the diagnosis of CDI.